MODIFIKASI UNIT KONTROL MEKANIK MESIN PRESS INCLINABLE UNTUK EFISIENSI PROSES PERBAIKAN KERUSAKAN PIN PENARIK RACK GEAR DI PT. SELAMAT SEMPURNA Tbk. - , VINCENTIUS YOBI K ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The damage at the machines will decrease the production targets. Therefore, the maintenance department that has a responsibility to repair the machines should do it quickly, so it can reduce the machine down time and the production process can be continued. There are many ways to speed up the repairing process. Those can reduce the machine downtime. One of them is modifying the machine components. At inclinable press machine, there is a part that often has damage. It is rack gear puller pin in mechanical control unit. At first to repair this damage is required 2 maintenance technicians. One technician removes the bolts of the body and someone else hold the body which has 15 kg weight. The component location is high and in a narrow place. It becomes an obstacle in the repairing process. Modifying the body is expected the repairing process will be more efficient than before. The result of this modification increases the efficiency of repairing time. Before the modification, the repairing process takes 52 minutes and after modifying, it takes 20 minutes. The efficiency also happens on the maintenance technician. It can be done by one techician only without bring down the all of components.